2021
DOI: 10.1055/s-0041-1730415
|View full text |Cite
|
Sign up to set email alerts
|

Embryo Glue: The Use of Hyaluronan in Embryo Transfer Media

Abstract: EmbryoGlue is available to patients at many in vitro fertilization clinics, usually at an additional cost. The efficacy of hyaluronan-enriched transfer medium (HETM) is supported by moderate quality evidence that indicates a significant improvement in clinical outcomes such as live birth rates for patients, including poorer prognosis women (i.e., maternal age factor [>35 years] and recurrent implantation failure). An increased multiple pregnancy rate has been reported with the use of HETM; therefore, a sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Yung et al in a randomized, double blind controlled trial involving 550 women concluded embryo glue use does not improve live birth rate following frozen embryo transfer [62]. In a review article Atkinson and Woodland concluded that the use of embryo glue may be justified for selected group of patients since there is no evidence to show any harmful effect [63]. However, higher pregnancy and live birth rates using embryo glue (hyaluronic acid) were observed in a Cochrane review of 16 randomized controlled trial [64].…”
Section: The Use Of Embryo Gluementioning
confidence: 99%
“…Yung et al in a randomized, double blind controlled trial involving 550 women concluded embryo glue use does not improve live birth rate following frozen embryo transfer [62]. In a review article Atkinson and Woodland concluded that the use of embryo glue may be justified for selected group of patients since there is no evidence to show any harmful effect [63]. However, higher pregnancy and live birth rates using embryo glue (hyaluronic acid) were observed in a Cochrane review of 16 randomized controlled trial [64].…”
Section: The Use Of Embryo Gluementioning
confidence: 99%